Design Optimization of Cesium Contents for Mixed Cation MA1−xCsxPbI3-Based Efficient Perovskite Solar Cell - Syed Abdul Moiz; Ahmed N. M. Alahmadi; Mohammed Saleh Alshaikh (Nanomaterials, 2025)
Perovskite solar cells (PSCs) have already been reported as a promising alternative to traditional energy sources due to their excellent power conversion efficiency, affordability, and versatility, which is particularly relevant considering the growing worldwide demand for energy and increasing scarcity of natural resources. However, operational concerns under environmental stresses hinder its economic feasibility. Through the addition of cesium (Cs), this study investigates how to optimize perovskite solar cells (PSCs) based on methylammonium lead-iodide (MAPbI3) by creating mixed-cation compositions of MA1−xCsxPbI3 (x = 0, 0.25, 0.5, 0.75, 1) for devices A to E, respectively. The impact of cesium content on the following factors, such as open-circuit voltage (Voc), short-circuit current density (Jsc), fill factor (FF), and power conversion efficiency (PCE), was investigated using simulation software, with ITO/TiO2/MA1−xCsxPbI3/Spiro-OMeTAD/Au as a device architecture. Due to diminished defect density, the device with x = 0.5 (MA0.5Cs0.5PbI3) attains a maximum power conversion efficiency of 18.53%, with a Voc of 0.9238 V, Jsc of 24.22 mA/cm2, and a fill factor of 82.81%. The optimal doping density of TiO2 is approximately 1020 cm−3, while the optimal thicknesses of the electron transport layer (TiO2, 10–30 nm), the hole-transport layer (Spiro-OMeTAD, about 10–20 nm), and the perovskite absorber (750 nm) were identified to maximize efficiency. The inclusion of a small amount of Cs may improve photovoltaic responses; however, at elevated concentrations (x > 0.5), power conversion efficiency (PCE) diminished due to the presence of trap states. The results show that mixed-cation perovskite solar cells can be a great commercially viable option because they strike a good balance between efficiency and performance.